Theoretical Aspects of Social Sensitivity in the Study of Social Ecology in Elementary Education - Pajar Sugilar; Nadiroh; Herlina Usman (International Conference on Elementary Education, 2023)
Social sensitivity is defined as the level of individual concern for others. Social sensitivity is a person's ability to react quickly and appropriately to certain social objects or situations around them. The environment around the child will greatly affect the child's social sensitivity. Contemporary social problems caused by current scientific and technological developments are a lack of social sensitivity. Most people in this era tend to be more selfish or individualistic. Whereas in principle, humans are social beings who cannot live without the help of other humans. Social sensitivity is able to improve a person's ability to make moral judgments, moral decision-making, and moral actions which are then applied in everyday life. form a person who has a high social awareness spirit. Social sensitivity starts from an adult person, and is able to direct it according to the moral values that exist in society. A person's personal maturity will be able to improve the quality of life he has both as an individual being and a social being. Therefore someone who is able to understand the moral values that exist in society will have a high level of social concern for the suffering of others and tends to have a high level of social sensitivity. The purpose of this research is to describe the aspects of social sensitivity in social ecological studies, namely empathy, prosociality and morality. Where this research method uses literature review which produces an overview of social sensitivity in social ecological studies in elementary schools.